PENGARUH HONEY MUMFORD DALAM MENINGKATKAN BERFIKIR KREATIF PESERTA DIDIK MAN 3 TAPANULI TENGAH - Ahmad Fadlan (Jurnal Akuntansi Bisnis dan Publik, 2020)
The formulation of the problem in this study is whether there is the influence of the Honey Mumford Model Learning Style in Increasing Students' Motivation and Creative Thinking Ability in Economic Subjects in Class XII of MAN 3 Middle Tapanuli in the school year 2018-2019 ?. The purpose of this study was to determine the Effect of Honey Mumford's Learning Style Model in Increasing Students' Motivation and Creative Thinking Ability in Economic Subjects of Class XII MAN 3 Middle Tapanuli academic year 2018-2019. The research method used was the Associative method. The formula used in this study is to use a statistical formula that is Product Moment correlation. From the calculation of the correlation coefficient, the results of r count = 1 are obtained, this result is then compared with rtable where r count is greater than rtable ie 1> 0.413, it can be said that there is the Effect of Honey Mumford Model Learning Style in Increasing Participants' Motivation and Creative Thinking Ability Educate in Economics Subject Class XII MAN 3 Middle Tapanuli academic year 2018-2019.